Analysis of pore geometry in the compacted fine aggregate matrix by x-ray microtomography (Brazilian Journal of Radiation Sciences (BJRS), 2022)
This study employs the advanced X-ray microtomography technique to evaluate the open and closed porosity geometry within fine aggregate matrix specimens extracted from different locations of SGC samples compacted with distinct densities. The adoption of advanced techniques such as the X-ray microtomography facilitate the fabrication of FAMs that are more representative of those that comprise asphalt concretes, as well as allow the use of similar replicates in mechanical tests. In addition, the traditional porosity assessment methods are well documented, but provide only global average results for the entire sample. In this context, X-ray microtomography stands out because, besides porosity information, pore distribution and a series of other parameters related to the internal structure of the object can be evaluated. This study evaluated the geometry of open and closed pores of FAM specimens extracted from different locations of SGC compacted samples. From the results and analyses, it can be concluded that the shape of the closed pores is spherical and the shape of the open pores is cylindrical for the SGC samples compressed with 2.26 g/cm3, 2.34 g/cm3 and 2.44 g/cm3.